Development Of Multi-Criteria Decision Making Model In Packed Beverage Industry Using Global Criterion Method - Sutrisno Sutrisno; Puryani Puryani (OPSI, 2021)
The packaged beverage industry with various brands has appeared on the market. The number of competitors in the market requires the packaged beverage industry to implement the right strategy to win the competition. One strategy that can be applied is to make savings and maximize the use of company resources. One of the savings that can be done is to minimize production costs, while maximizing the use of resources can be done by maximizing the utility of the machine owned by the company. Efforts to minimize production costs can be contradictory to efforts to maximize machine utility, this is because maximizing machine utility will certainly require additional production costs, even though the company also wants to minimize production costs. This is included in the category of multi-criteria decision-making problems. To facilitate the company's management in achieving these contradictory company goals, this study will develop a multi-criteria decision-making model to assist companies in making optimal decisions regarding these contradictory company goals. The multi-criteria decision-making model developed is a mathematical model consisting of two mutually contradictory objective functions, namely minimizing production costs and maximizing machine utility, as well as problem constraints which are limitations that are owned by the company in optimizing the achievement of these contradictory company goals. To optimize the multi-criteria decision-making model that has been developed, it will use the global criterion method. The global criterion method will produce a compromise solution that has a minimum deviation from the ideal value of each objective function. Using the global criterion method, a production plan that minimizes production costs and maximizes machine utility is obtained. The multi-criteria decision-making model developed will cause the production plan to have a small deviation from the actual demand, because the model development involves forecasting product demand. The developed model will also produce a production plan that will not exceed the warehouse capacity, so that product storage costs can be minimized, this is because the developed model includes warehouse capacity as a barrier.